Photocurable resin composition, adhesive sheet and method for manufacturing laminate
By using a photocurable resin composition containing a specific monomer and a thermoplastic resin, the problems of insufficient oxygen barrier and creep retention during the photocuring process are solved, and the effects of high adhesion and creep resistance are achieved.
Patent Information
- Application Number
- CN202380063115.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-01
- Filing Date
- 2023-11-30
- Publication Date
- 2025-03-28
AI Technical Summary
The conventional photocurable resin composition is susceptible to oxygen during the curing process, resulting in insufficient curing of the surface, affecting the adhesiveness, and at the same time, the creep retention force is also low, making it difficult to take into account both adhesion and creep resistance.
The photocurable resin composition containing monofunctional (meth)acrylic monomer, multifunctional (meth)acrylic monomer, photopolymerization initiator, and thermoplastic resin having block structure or graft structure is used to adjust its viscosity between 0.001 Pa·s and 500 Pa·s to improve adhesion and creep resistance.
It achieves efficient curing in the presence of oxygen, ensures surface adhesion, and improves creep retention force, achieving excellent adhesion and creep resistance.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to a photocurable resin composition, a pressure-sensitive adhesive sheet formed using the photocurable resin composition, and a method for producing a laminate using the photocurable resin composition. Background Art
[0002] In the interior of electronic devices such as smart phones and PCs, adhesives are used in the lamination of electronic components. In the usual method of laminating with adhesives, first, an adhesive sheet with spacers respectively arranged on both sides of the adhesive is made, and then the adhesive sheet is cut into a desired shape. Then, a spacer is peeled off from the cut adhesive sheet, and one side of the exposed adhesive is laminated with the first adherend, and then another spacer is peeled off, and the other side of the exposed adhesive is laminated with the second adherend. In the case of this method, since a part of the adhesive sheet is discarded after cutting, waste will be generated.
[0003] In view of this, a method of printing a pressure-sensitive adhesive composition into a desired shape and then bonding it to an adherend has been studied. This method can suppress the generation of waste.
[0004] As an invention of an adhesive composition that can be used in such a method, for example, Patent Document 1 discloses an invention for providing a radiation-curable adhesive composition that can be finely patterned and exhibits high adhesion to various adherends such as metals and plastics. Patent Document 1 describes a radiation-curable adhesive composition containing 10 to 70% by weight of an ethylenically unsaturated monomer that does not contain an aromatic ring, 1 to 10% by weight of a photopolymerization initiator, and 10 to 55% by weight of a crosslinking agent.
[0005] In addition, Patent Document 2 discloses an invention for providing a photocurable adhesive composition that provides a laminate having an adhesive strength equivalent to that in the absence of oxygen even when light irradiation is performed in the presence of oxygen. Patent Document 2 describes a photocurable adhesive composition comprising (A) a (meth)acrylate oligomer, (B) a monofunctional (meth)acrylic monomer, (C) a 2- to 4-functional (meth)acrylic monomer, (D) a photoreaction initiator, (E) a tackifier having a softening point of 70 to 150° C., and (F) a liquid plasticizer.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2013-216742
[0009] Patent Document 2: International Publication No. 2016 / 163152 Summary of the invention
[0010] Problems to be solved by the invention
[0011] As mentioned above, according to the method of laminating with adherend after printing adhesive composition into desired shape, the generation of waste can be suppressed.On the other hand, as the method for curing adhesive composition, in order to avoid the heating of adherend, it is desirable to utilize the method of light irradiation, but if adhesive composition is not covered by separator and exposed in the presence of oxygen when curing, the outermost surface is uncured, and adhesion cannot be fully obtained sometimes.Therefore, in order to prevent oxygen from hindering, it is necessary to seal adhesive composition with separator, irradiate light under inert gas atmosphere and make reaction proceed.In addition, even when using the material that is not easily hindered by oxygen to improve adhesion, creep retention is sometimes also lowered, requiring adhesion and creep resistance these two excellent photocurable resin compositions.
[0012] An object of the present invention is to provide a photocurable resin composition having excellent adhesiveness and creep resistance. Another object of the present invention is to provide a pressure-sensitive adhesive sheet using the photocurable resin composition and a method for producing a laminate using the photocurable resin composition.
[0013] Means for solving problems
[0014] The present disclosure 1 relates to a photocurable resin composition, which contains a monofunctional (meth)acrylic monomer, a multifunctional (meth)acrylic monomer, a photopolymerization initiator and a thermoplastic resin, wherein the thermoplastic resin has a block structure or a graft structure, and the viscosity of the photocurable resin composition at 25° C. is greater than or equal to 0.001 Pa·s and less than or equal to 500 Pa·s.
[0015] Present Disclosure 2 relates to the photocurable resin composition of Present Disclosure 1, wherein the thermoplastic resin includes a thermoplastic resin having a structure derived from styrene.
[0016] The present disclosure 3 relates to the photocurable resin composition of the present disclosure 2, wherein the thermoplastic resin having a structure derived from styrene is a (meth)acrylic acid / styrene copolymer.
[0017] The present disclosure 4 is related with the photocurable resin composition of the present disclosure 2 or 3, wherein the content ratio of the structure derived from styrene in the thermoplastic resin having a structure derived from styrene is 3% by mass or more.
[0018] The present disclosure 5 relates to the photocurable resin composition of the present disclosure 1, 2, 3 or 4, wherein the thermoplastic resin includes a triblock copolymer, and the content ratio of the triblock copolymer in the thermoplastic resin is 50% by mass or more.
[0019] The present disclosure 6 relates to the photocurable resin composition of the present disclosure 1, 2, 3, 4 or 5, wherein the weight average molecular weight of the thermoplastic resin is 100,000 or more and 500,000 or less.
[0020] The present disclosure 7 relates to the photocurable resin composition of the present disclosure 1, 2, 3, 4, 5 or 6, wherein the content ratio of the thermoplastic resin in the photocurable resin composition is 1% by mass or more and 60% by mass or less.
[0021] The present disclosure 8 relates to the photocurable resin composition of the present disclosure 7, wherein the content ratio of the thermoplastic resin in the photocurable resin composition is 10% by mass or more and 40% by mass or less.
[0022] The present disclosure 9 relates to the photocurable resin composition of the present disclosure 1, 2, 3, 4, 5, 6, 7 or 8, wherein the content ratio of the polyfunctional (meth)acrylic monomer in the photocurable resin composition is 0.3 mass % or more and 40 mass % or less.
[0023] The present disclosure 10 relates to the photocurable resin composition of the present disclosure 1, 2, 3, 4, 5, 6, 7, 8 or 9, wherein the irradiation dose is 3000 mJ / cm 2 The photocurable resin composition was irradiated with a wavelength of 395 nm and an illumination of 500 mW / cm 2 The ultraviolet rays obtained by the curing process have a gel fraction of 25% by mass or more and 60% by mass or less.
[0024] The present disclosure 11 relates to a pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer containing a cured product of the photocurable resin composition of the present disclosure 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10.
[0025] The present disclosure 12 relates to the pressure-sensitive adhesive sheet of the present disclosure 11, which comprises a substrate and a pressure-sensitive adhesive layer located on at least one surface of the substrate and containing a cured product of the photocurable resin composition.
[0026] The present disclosure 13 relates to a method for producing a laminate, comprising: a step of printing the photocurable resin composition of the present disclosure 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10; and a step of attaching an adherend using the printed photocurable resin composition.
[0027] The present disclosure 14 relates to the method for producing a laminated body according to the present disclosure 13, wherein the method for printing the photocurable resin composition is screen printing, inkjet printing or flexographic printing.
[0028] Hereinafter, the present invention will be described in detail.
[0029] From the viewpoint of printability, the present inventors studied that a photocurable resin composition contains a monofunctional (meth)acrylic monomer, a polyfunctional (meth)acrylic monomer, a photopolymerization initiator, and a thermoplastic resin having a block structure or a graft structure while adjusting the viscosity to a specific range. As a result, they found that a photocurable resin composition having excellent adhesiveness and creep resistance can be obtained, and thus completed the present invention.
[0030] The photocurable resin composition of the present invention contains a monofunctional (meth)acrylic monomer.
[0031] The monofunctional (meth)acrylic monomer is a polymerizable monomer that is polymerized by a reaction with a photopolymerization initiator described below. By containing the monofunctional (meth)acrylic monomer, the photocurable resin composition of the present invention has excellent adhesion to various substrates.
[0032] It should be noted that, in this specification, the above-mentioned "(meth)acrylic acid" refers to acrylic acid or methacrylic acid, the above-mentioned "(meth)acrylic monomer" refers to a monomer having a (meth)acryloyl group, and the above-mentioned "(meth)acryloyl group" refers to an acryloyl group or a methacryloyl group. In addition, in this specification, the above-mentioned "monofunctional (meth)acrylic monomer" refers to a monomer having one (meth)acryloyl group in one molecule.
[0033] Examples of the monofunctional (meth)acrylic monomer include monofunctional (meth)acrylate compounds, monofunctional (meth)acrylamide compounds, and monofunctional (meth)acrylimide compounds.
[0034] Examples of the monofunctional (meth)acrylate compound include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, n-heptyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, isomyristyl (meth)acrylate, stearyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, and 2-hydroxy-3-phenoxypropyl (meth)acrylate. 2-Hydroxybutyl (meth)acrylate, 4-Hydroxybutyl (meth)acrylate, Cyclohexyl (meth)acrylate, Isobornyl (meth)acrylate, Dicyclopentenyl (meth)acrylate, Benzyl (meth)acrylate, 2-Methoxyethyl (meth)acrylate, 2-Ethoxyethyl (meth)acrylate, 2-Butoxyethyl (meth)acrylate, 2-Phenoxyethyl (meth)acrylate, Methoxyethylene glycol (meth)acrylate, Methoxypolyethylene glycol (meth)acrylate, Phenoxydiethylene glycol (meth)acrylate, Phenoxypolyethylene glycol (meth)acrylate, Tetrahydrofurfuryl (meth)acrylate, Tetrahydrofurfuryl alcohol acrylate polymer Ethyl carbitol (meth)acrylate, 2,2,2-trifluoroethyl (meth)acrylate, 2,2,3,3-tetrafluoropropyl (meth)acrylate, 1H,1H,5H-octafluoropentyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, 2-(meth)acryloyloxyethyl succinate, 2-(meth)acryloyloxyethyl hexahydrophthalate, 2-(meth)acryloyloxyethyl 2-hydroxypropyl phthalate, 2-(meth)acryloyloxyethyl phosphate, (3-ethyloxetan-3-yl)methyl (meth)acrylate, 2-(((butylamino)carbonyl)oxy) (meth)acrylate ethyl (meth)acrylate, (3-propyloxetane-3-yl)methyl (meth)acrylate, (3-butyloxetane-3-yl)methyl (meth)acrylate, (3-ethyloxetane-3-yl)ethyl (meth)acrylate, (3-ethyloxetane-3-yl)propyl (meth)acrylate, (3-ethyloxetane-3-yl)butyl (meth)acrylate, (3-ethyloxetane-3-yl)pentyl (meth)acrylate, (3-ethyloxetane-3-yl)hexyl (meth)acrylate, γ-butyrolactone (meth)acrylate, (2,2-dimethyl-1,3-dioxolan-4-yl)methyl (meth)acrylate, (2-methyl-2-ethyl-1,3-dioxolan-4-yl) methyl ester, (meth)acrylate (2-methyl-2-isobutyl-1,3-dioxolan-4-yl) methyl ester, (meth)acrylate (2-cyclohexyl-1,3-dioxolan-4-yl) methyl ester, cyclic trimethylolpropane formal acrylate, etc.
[0035] It should be noted that, in the present specification, the above-mentioned “(meth)acrylate” means acrylate or methacrylate.
[0036] Examples of the monofunctional (meth)acrylamide compound include N,N-dimethyl (meth)acrylamide, N-(meth)acryloylmorpholine, N-hydroxyethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N-isopropyl (meth)acrylamide, and N,N-dimethylaminopropyl (meth)acrylamide.
[0037] As said monofunctional (meth)acrylimide compound, N-(meth)acryloyloxyethylhexahydrophthalimide etc. are mentioned, for example.
[0038] The preferred lower limit of the content of the monofunctional (meth) acrylic monomer in the photocurable resin composition of the present invention is 20% by mass, and the preferred upper limit is 90% by mass. By making the content of the monofunctional (meth) acrylic monomer within this range, the adhesion of the obtained photocurable resin composition to various substrates becomes more excellent. The more preferred lower limit of the content of the monofunctional (meth) acrylic monomer is 30% by mass, and the more preferred upper limit is 85% by mass.
[0039] The photocurable resin composition of the present invention contains a polyfunctional (meth)acrylic monomer.
[0040] The polyfunctional (meth)acrylic monomer is a polymerizable monomer that is polymerized by a reaction of a photopolymerization initiator described below, and the polyfunctional (meth)acrylic monomer has a function as a cross-linking component.
[0041] In addition, in this specification, the said "polyfunctional (meth)acrylic-based monomer" means a monomer which has two or more (meth)acryloyl groups in one molecule.
[0042] Examples of the polyfunctional (meth)acrylic monomer include polyfunctional urethane (meth)acrylates, polyfunctional (meth)acrylate compounds, and polyfunctional epoxy (meth)acrylates.
[0043] In addition, in this specification, the said "epoxy (meth)acrylate" means the compound obtained by making all epoxy groups in an epoxy compound react with (meth)acrylic acid.
[0044] The polyfunctional urethane (meth)acrylate can be obtained, for example, by reacting a (meth)acrylic acid derivative having a hydroxyl group with an isocyanate compound in the presence of a catalytic amount of a tin-based compound.
[0045] Examples of the isocyanate compound used as a raw material for the polyfunctional urethane (meth)acrylate include isophorone diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, diphenylmethane-4,4′-diisocyanate (MDI), hydrogenated MDI, polymeric MDI, 1,5-naphthalene diisocyanate, norbornane diisocyanate, dimethylbiphenyl diisocyanate, xylylene diisocyanate (XDI), hydrogenated XDI, lysine diisocyanate, triphenylmethane triisocyanate, tris(isocyanatephenyl)phosphorothioate, tetramethylxylylene diisocyanate, and 1,6,11-undecane triisocyanate.
[0046] Furthermore, as the isocyanate compound serving as a raw material of the polyfunctional urethane (meth)acrylate, a chain-extended isocyanate compound obtained by a reaction between a polyol and an excess of an isocyanate compound may be used.
[0047] Examples of the polyol include ethylene glycol, propylene glycol, glycerin, sorbitol, trimethylolpropane, carbonate diol, polyether diol, polyester diol, and polycaprolactone diol.
[0048] Examples of the (meth)acrylic acid derivative having a hydroxyl group include hydroxyalkyl mono(meth)acrylates, mono(meth)acrylates of diols, and mono(meth)acrylates or di(meth)acrylates of triols.
[0049] Examples of the hydroxyalkyl mono(meth)acrylate include 2-hydroxyethyl(meth)acrylate, 2-hydroxypropyl(meth)acrylate, 2-hydroxybutyl(meth)acrylate, and 4-hydroxybutyl(meth)acrylate.
[0050] Examples of the diol include ethylene glycol, propylene glycol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, and polyethylene glycol.
[0051] Examples of the triol include trimethylolethane, trimethylolpropane, and glycerin.
[0052] Examples of the polyfunctional (meth)acrylate compound include 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, 2-n-butyl-2-ethyl-1,3-propanediol di(meth)acrylate, and 1,9-nonanediol di(meth)acrylate. (Meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, ethylene oxide added bisphenol A di(meth)acrylate, propylene oxide added bisphenol A di(meth)acrylate, ethylene oxide added bisphenol F di(meth)acrylate, dimethylol dicyclopentadienyl di(meth)acrylate, ethylene oxide modified isocyanuric acid di(meth)acrylate, 2-hydroxy-3-(meth)acryloyloxypropyl (meth)acrylate Ester, carbonate diol di(meth)acrylate, polyether diol di(meth)acrylate, polyester diol di(meth)acrylate, polycaprolactone diol di(meth)acrylate, polybutadiene diol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, ethylene oxide added trimethylolpropane tri(meth)acrylate, propylene oxide added trimethylolpropane tri(meth)acrylate, caprolactone modified trimethylolpropane tri(meth)acrylate, tetramethylolmethane tetra(meth)acrylate Acrylate, ethylene oxide added isocyanuric acid tri(meth)acrylate, glycerol tri(meth)acrylate, propylene oxide added glycerol tri(meth)acrylate, pentaerythritol tri(meth)acrylate, tri(meth)acryloyloxyethyl phosphate, di(trimethylolpropane) tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol monohydroxy penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, caprolactone modified dipentaerythritol hexa(meth)acrylate, etc.
[0053] Examples of the polyfunctional epoxy (meth)acrylate include bisphenol A epoxy (meth)acrylate, bisphenol F epoxy (meth)acrylate, bisphenol E epoxy (meth)acrylate, and caprolactone-modified products thereof.
[0054] The preferred lower limit of the content of the multifunctional (meth) acrylic monomer in the photocurable resin composition of the present invention is 0.3% by mass, and the preferred upper limit is 40% by mass. By making the content of the multifunctional (meth) acrylic monomer within this range, the adhesion and creep resistance of the obtained photocurable resin composition to various substrates become more excellent. The more preferred lower limit of the content of the multifunctional (meth) acrylic monomer is 0.5% by mass, and the more preferred upper limit is 30% by mass.
[0055] The photocurable resin composition of the present invention preferably contains a compound having a cyclic structure containing a nitrogen atom (hereinafter also referred to as a "nitrogen-containing ring compound") as a polymerizable monomer. By containing the nitrogen-containing ring compound, the photocurable property of the obtained photocurable resin composition in the presence of oxygen becomes more excellent. The nitrogen-containing ring compound may be contained in the monofunctional (meth)acrylic monomer or the polyfunctional (meth)acrylic monomer, or may not be contained in the monofunctional (meth)acrylic monomer or the polyfunctional (meth)acrylic monomer.
[0056] The nitrogen-containing ring compound preferably includes at least one selected from a monofunctional radical polymerizable monomer having a lactam structure and a maleimide derivative, and more preferably includes a maleimide derivative.
[0057] The reaction system of the monofunctional free radical polymerizable monomer having a lactam structure and the maleimide derivative is basically carried out through a hydrogen abstraction (Type II) reaction. The photoradical polymerization based on the hydrogen abstraction reaction is not easily hindered by oxygen, so the surface curability can be improved. In addition, in the photoradical polymerization based on the hydrogen abstraction reaction, a branched polymer is obtained instead of a linear polymer as in the cleavage (Type I) reaction, and the cohesion is also increased. Therefore, by containing the monofunctional free radical polymerizable monomer having a lactam structure and the maleimide derivative, the photocurable resin composition obtained can obtain a cured product that is less likely to have bleeding accompanied by reduced surface curability and cohesive failure accompanied by reduced surface curability and cohesion.
[0058] Examples of the monofunctional maleimide in the maleimide derivatives include N-cyclohexylmaleimide, N-laurylmaleimide, 4-hydroxyphenylmaleimide, N-(4-carboxycyclohexylmethyl)maleimide, N-phenylmaleimide, N-(2-methylphenyl)maleimide, N-(4-methylphenyl)maleimide, N-(2,6-diethylphenyl)maleimide, N-(2-chlorophenyl)maleimide, N-methylmaleimide, and N-ethyl Maleimide, N-isopropylmaleimide, N-butylmaleimide, N-benzylmaleimide, N-phenylmethylmaleimide, N-(2,4,6-tribromophenyl)maleimide, N-(3-(triethoxysilyl)propyl)maleimide, N-octadecenylmaleimide, N-dodecenylmaleimide, N-(2-methoxyphenyl)maleimide, N-(2,4,6-trichlorophenyl)maleimide, N-(1-hydroxyphenyl)maleimide, etc. Among them, from the viewpoint of improving the reaction rate, it is desirable to select a maleimide derivative having a structure that does not hydrogen bond to a hetero atom. In addition, from the viewpoint of improving the adhesive force, a maleimide derivative having a structure that hydrogen bonds to a hetero atom can be used. Specifically, the monofunctional maleimide is preferably at least one selected from N-cyclohexylmaleimide, 4-hydroxyphenylmaleimide, and N-(4-carboxycyclohexylmethyl)maleimide, and more preferably N-cyclohexylmaleimide.
[0059] Examples of the polyfunctional maleimide in the maleimide derivatives include N,N'-methylenebismaleimide, N,N'-trimethylenebismaleimide, N,N'-dodecamethylenebismaleimide, N,N'-(4,4'-diphenylmethane)bismaleimide, 1,4-dimaleimide cyclohexane, isophoronebiscarbamate bis(N-ethylmaleimide), N,N'-p-phenylenebismaleimide, N,N'-m-phenylenebismaleimide, N,N'-m-toluenebismaleimide, and N,N'-4,4 '-biphenylene bismaleimide, N,N'-4,4'-(3,3'-dimethyl-biphenylene) bismaleimide, N,N'-4,4'-(3,3'-dimethyldiphenylmethane) bismaleimide, N,N'-4,4'-(3,3'-diethyldiphenylmethane) bismaleimide, N,N'-4,4'-diphenylpropane bismaleimide, N,N'-4,4'-diphenylether bismaleimide, N,N'-3,3'-diphenylsulfone bismaleimide, N,N'-4,4'-diphenylsulfone bismaleimide, etc. From the viewpoint of improving the reaction rate, as the maleimide derivative, the monofunctional maleimide and these polyfunctional maleimides may be used in combination, but since the gel fraction increases, it is not preferred to use a large amount of polyfunctional maleimide in combination.
[0060] The monofunctional radical polymerizable monomer having a lactam structure is preferably a compound represented by the following formula (1).
[0061] [Chemical formula 1]
[0062]
[0063] In formula (1), n represents an integer of 2 to 6.
[0064] Examples of the compound represented by the formula (1) include N-vinyl-2-pyrrolidone and N-vinyl-ε-caprolactam. Among them, N-vinyl-ε-caprolactam is preferred.
[0065] The preferred lower limit of the content ratio of the above-mentioned nitrogen-containing ring compound in the photocurable resin composition of the present invention is 0.1% by mass, and the preferred upper limit is 30% by mass. By making the content ratio of the above-mentioned nitrogen-containing ring compound within this range, the surface curability and adhesion to various substrates of the obtained adhesive sheet become more excellent. The more preferred lower limit of the content ratio of the above-mentioned nitrogen-containing ring compound is 0.5% by mass, and the more preferred upper limit is 25% by mass.
[0066] The photocurable resin composition of the present invention contains a photopolymerization initiator.
[0067] The photopolymerization initiator preferably includes at least one selected from a hydrogen abstraction type photopolymerization initiator and a polymer type photopolymerization initiator. By using at least one selected from the hydrogen abstraction type photopolymerization initiator and the polymer type photopolymerization initiator as the photopolymerization initiator, the obtained cured product is less likely to bleed out due to reduced surface curability and cohesive failure due to reduced surface curability and cohesive force. The photopolymerization initiator more preferably includes a polymer type photopolymerization initiator.
[0068] Examples of the polymeric photopolymerization initiator include polymers of ethyl (2,4,6-trimethylbenzoyl)-phenylphosphonate, polyethylene glycol di(β-4(4-(2-dimethylamino-2-benzyl)butyrylphenyl)piperazine)propionate, and polyethylene glycol bis(benzophenone-2-carboxylate).
[0069] Examples of commercially available products of the polymer-type photopolymerization initiator include Omnipol TP, Omnipol 910, and Omnipol 2702 (all manufactured by IGM Resins Co., Ltd.).
[0070] As the hydrogen abstraction type photopolymerization initiator, a benzophenone-based photopolymerization initiator is preferred. Examples of the benzophenone-based photopolymerization initiator include benzophenone, 4-chlorobenzophenone, 4,4′-dimethylbenzophenone, 4-methylbenzophenone, 2,4,6-trimethylbenzophenone, methyl o-benzoylbenzoate, 3,3′-dimethyl-4-methoxybenzophenone, 4-phenylbenzophenone, 4-benzoyl-4′-methyl-diphenyl sulfide, 4-morpholinobenzophenone, 4,4′-diphenoxybenzophenone, 4-hydroxybenzophenone, 2-carboxybenzophenone, 2-hydroxy-1-(4-(4-(2-hydroxy-2-methyl-propionyl)-benzyl)-phenyl)-2-methyl-propane-1-one, 1-(4-(4-benzoylphenylthio)phenyl)-2-tosyl-2-methyl-1-propanone, and 3-coumarinone.
[0071] As the photopolymerization initiator, a cleavage-type photopolymerization initiator may be used.
[0072] Examples of the cleavage-type photopolymerization initiator include 1-hydroxycyclohexyl phenyl ketone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide.
[0073] The preferred lower limit of the content of the photopolymerization initiator in the photocurable resin composition of the present invention is 1% by mass, and the preferred upper limit is 15% by mass. By making the content of the photopolymerization initiator within this range, the storage stability and curability of the obtained photocurable resin composition become more excellent, and the adhesion of the obtained adhesive sheet to various substrates becomes more excellent. The more preferred lower limit of the content of the photopolymerization initiator is 3% by mass, and the more preferred upper limit is 8% by mass.
[0074] The photocurable resin composition of the present invention contains a thermoplastic resin.
[0075] The above-mentioned thermoplastic resin has a block structure or a graft structure.
[0076] By containing the thermoplastic resin having the block structure or the graft structure, the photocurable resin composition of the present invention has excellent creep resistance. Among them, the thermoplastic resin preferably has a block structure.
[0077] It should be noted that the block structure or the graft structure may exist in any part of the molecule of the thermoplastic resin, and a random structure may exist in other parts. In addition, even if the thermoplastic resin is a polymer of two or more monomers having a common structure, when the two or more monomers are different compounds and have a block structure or a graft structure, it is also regarded as a thermoplastic resin having a block structure or a graft structure. As such an example, an acrylic triblock copolymer derived from three acrylic monomers can be cited.
[0078] The thermoplastic resin preferably includes a thermoplastic resin having a structure derived from styrene or a thermoplastic resin having a structure derived from a (meth) acrylic compound. By including the thermoplastic resin having a structure derived from styrene or a thermoplastic resin having a structure derived from a (meth) acrylic compound, the creep resistance of the obtained photocurable resin composition becomes more excellent. Among them, the thermoplastic resin more preferably includes a thermoplastic resin having a structure derived from styrene.
[0079] Examples of the thermoplastic resin having a structure derived from styrene include (meth)acrylic acid / styrene copolymers, butadiene / styrene, isoprene / styrene, ethylene butylene / styrene, ethylene propylene / styrene, etc. Among them, (meth)acrylic acid / styrene copolymers are preferred from the viewpoint of improving compatibility with monofunctional (meth)acrylic monomers and polyfunctional (meth)acrylic monomers and creep resistance.
[0080] The preferred lower limit of the content of the structure derived from styrene in the thermoplastic resin having a structure derived from styrene is 3% by mass. By making the content of the structure derived from styrene 3% or more by mass, the creep resistance of the obtained photocurable resin composition becomes more excellent. The more preferred lower limit of the content of the structure derived from styrene is 4% by mass.
[0081] In addition, from the viewpoint of compatibility with monofunctional (meth) acrylic monomers and polyfunctional (meth) acrylic monomers and adhesion to adherends, the preferred upper limit of the content of the above-mentioned styrene-derived structure in the above-mentioned thermoplastic resin having a styrene-derived structure is 40% by mass, and the more preferred upper limit is 30% by mass.
[0082] Examples of the thermoplastic resin having a structure derived from a (meth)acrylic compound include poly(meth)acrylates, acrylonitrile / styrene / (meth)acrylic acid copolymers, (meth)acrylic acid / styrene copolymers, ethylene / (meth)acrylic acid copolymers / acrylic acid / methacrylic acid copolymers, etc. Among them, (meth)acrylic acid / styrene copolymers are preferred from the viewpoint of improving compatibility with monofunctional (meth)acrylic acid monomers and polyfunctional (meth)acrylic acid monomers and creep resistance.
[0083] The thermoplastic resin preferably includes a triblock copolymer. By including the thermoplastic resin as the triblock copolymer, the creep resistance of the obtained photocurable resin composition becomes more excellent.
[0084] Among them, the thermoplastic resin more preferably includes a (meth)acrylic acid / styrene triblock copolymer which is an ABA type triblock copolymer.
[0085] The preferred lower limit of the content of the above-mentioned triblock copolymer in the above-mentioned thermoplastic resin is 50% by mass. By making the content of the above-mentioned triblock copolymer 50% by mass or more, the creep resistance of the obtained photocurable resin composition becomes more excellent. The more preferred lower limit of the content of the above-mentioned triblock copolymer is 70% by mass.
[0086] In addition, the content ratio of the triblock copolymer may be 100% by mass, that is, the thermoplastic resin may contain only the triblock copolymer.
[0087] The preferred lower limit of the weight average molecular weight of the thermoplastic resin is 100,000, and the preferred upper limit is 500,000. By making the weight average molecular weight of the thermoplastic resin within this range, the creep resistance of the obtained photocurable resin composition becomes more excellent. The more preferred lower limit of the weight average molecular weight of the thermoplastic resin is 150,000, and the more preferred upper limit is 400,000.
[0088] The weight average molecular weight can be determined, for example, by measuring the molecular weight distribution in terms of polystyrene using gel permeation chromatography (GPC). Specifically, it can be determined, for example, by measuring using gel permeation chromatography (such as "2690 Separations Module" manufactured by Waters Corporation) under the following conditions.
[0089] Solvent: Tetrahydrofuran
[0090] Sample flow rate: 1mL / min
[0091] Detector: Differential Refractometer RI
[0092] Column: GPC KF-806L (manufactured by Showa Denko K.K.)
[0093] Column temperature (measurement temperature): 40°C
[0094] Injection volume: 20 μL
[0095] The preferred lower limit of the content of the thermoplastic resin in the photocurable resin composition of the present invention is 1% by mass, and the preferred upper limit is 60% by mass. By making the content of the thermoplastic resin within this range, the creep resistance of the obtained photocurable resin composition becomes more excellent. The more preferred lower limit of the content of the thermoplastic resin is 10% by mass, and the more preferred upper limit is 40% by mass.
[0096] The photocurable resin composition of the present invention preferably further contains a tackifier.
[0097] Examples of the tackifier include rosin-based resins and terpene-based resins.
[0098] Examples of the rosin-based resin include rosin diol and the like.
[0099] The above-mentioned rosin diol is not particularly limited as long as it is a rosin-modified diol having a rosin skeleton and two hydroxyl groups in the molecule. A diol having a rosin component in the molecule is called a rosin polyol, and the skeleton other than the rosin component includes a polyether type such as polypropylene glycol (PPG), and a polyester type such as a condensed polyester polyol, a lactone polyester polyol, and a polycarbonate diol.
[0100] Examples of the rosin diol include rosin esters obtained by reacting rosin with a polyol, epoxy-modified rosin esters obtained by reacting rosin with an epoxy compound, and modified rosins having a hydroxyl group such as polyether having a rosin skeleton. These can be produced by conventionally known methods.
[0101] Examples of the rosin component include rosin acid derivatives such as abietic acid, dehydroabietic acid, dihydroabietic acid, tetrahydroabietic acid, disabietic acid, and neoabietic acid; pimaric acid-type resin acids such as levorotatory pimaric acid; hydrogenated rosins obtained by hydrogenating these; and disproportionated rosins obtained by disproportionating these.
[0102] Examples of commercially available products of the rosin-based resins include PINECRYSTAL D-6011, PINECRYSTAL KE-615-3, PINECRYSTAL KR-614, PINECRYSTAL KE-100, PINECRYSTAL KE-311, PINECRYSTAL KE-359, PINECRYSTAL KE-604, and PINECRYSTAL D-6250 (all manufactured by Arakawa Chemical Industries, Ltd.).
[0103] Examples of the terpene resin include terpene phenol resins and the like.
[0104] The above-mentioned terpene-phenol resin refers to a copolymer of a terpene resin which is an essential oil component obtained from natural products such as rosin and orange peel and phenol, and also includes a partially hydrogenated terpene-phenol resin obtained by hydrogenating at least a portion of the copolymer or a fully hydrogenated terpene-phenol resin obtained by fully hydrogenating the copolymer.
[0105] Here, the fully hydrogenated terpene-phenol resin is a terpene-phenol resin obtained by substantially fully hydrogenating the terpene-phenol resin, and the partially hydrogenated terpene-phenol resin is a terpene-phenol resin obtained by partially hydrogenating the terpene-phenol resin. In addition, the terpene-phenol resin has double bonds derived from terpenes and aromatic ring double bonds derived from phenols. Therefore, the fully hydrogenated terpene-phenol resin refers to a resin in which both the terpene part and the phenol part are completely or almost hydrogenated, and the partially hydrogenated terpene-phenol resin refers to a resin in which the degree of hydrogenation of these parts is not complete but partially hydrogenated. There is no particular limitation on the method and reaction form for the above-mentioned hydrogenation.
[0106] Examples of commercially available products of the terpene-phenol resins include YS Polyster NH (completely hydrogenated terpene-phenol resin) manufactured by Yasuhara Chemical Co., Ltd., and the like.
[0107] The preferred lower limit of the content ratio of the above-mentioned tackifier in the photocurable resin composition of the present invention is 5% by mass, and the preferred upper limit is 50% by mass. By making the content ratio of the above-mentioned tackifier within this range, the adhesion of the obtained photocurable resin composition to various substrates becomes more excellent. The more preferred lower limit of the content ratio of the above-mentioned tackifier is 10% by mass, and the more preferred upper limit is 40% by mass.
[0108] The photocurable resin composition of the present invention may contain a filler from the viewpoint of improving printability by adjusting the viscosity.
[0109] As the filler, an inorganic filler or an organic filler can be used.
[0110] Examples of the inorganic filler include silica, talc, glass beads, asbestos, gypsum, diatomaceous earth, smectite, bentonite, montmorillonite, sericite, activated clay, aluminum oxide, zinc oxide, iron oxide, magnesium oxide, tin oxide, titanium oxide, calcium carbonate, magnesium carbonate, magnesium hydroxide, aluminum hydroxide, aluminum nitride, silicon nitride, barium sulfate, and calcium silicate.
[0111] Examples of the organic filler include polyester microparticles, polyurethane microparticles, vinyl polymer microparticles, and (meth)acrylic polymer microparticles.
[0112] Among them, silicon dioxide is preferred, and fumed silica is more preferred.
[0113] The preferred lower limit of the content of the filler in the photocurable resin composition of the present invention is 0.3% by mass, and the preferred upper limit is 15% by mass. By making the content of the filler within this range, the obtained photocurable resin composition maintains excellent adhesion and is easy to adjust viscosity. The more preferred lower limit of the content of the filler is 0.5% by mass, and the more preferred upper limit is 10% by mass.
[0114] The photocurable resin composition of the present invention may contain a defoaming agent from the viewpoint of improving printability and the like.
[0115] Examples of the defoaming agent include silicone-based defoaming agents, acrylic polymer-based defoaming agents, vinyl ether polymer-based defoaming agents, and olefin polymer-based defoaming agents.
[0116] The preferred lower limit of the content of the above-mentioned defoamer in the photocurable resin composition of the present invention is 0.3% by mass, and the preferred upper limit is 5% by mass. By making the content of the above-mentioned defoamer within this range, the printability of the obtained photocurable resin composition becomes more excellent. The more preferred lower limit of the content of the above-mentioned defoamer is 0.5% by mass, and the more preferred upper limit is 3% by mass.
[0117] The photocurable resin composition of the present invention may further contain various known additives such as a plasticizer, a silane coupling agent, a sensitizer, a thermosetting agent, a curing retarder, an antioxidant, a storage stabilizer, and a dispersant within a range not hindering the purpose of the present invention.
[0118] Furthermore, from the viewpoint of preventing a decrease in photoreactivity, the photocurable resin composition of the present invention preferably contains substantially no organic solvent. Specifically, the content of the organic solvent in the photocurable resin composition is preferably 1.5% by mass or less.
[0119] As a method for preparing the photocurable resin composition of the present invention, for example, there can be mentioned a method of mixing the monofunctional (meth) acrylic monomer, the polyfunctional (meth) acrylic monomer, the photopolymerization initiator, the thermoplastic resin, and additives added as needed using a mixer, etc. Examples of the mixer include a homodispersor, a homomixer, a universal mixer, a planetary mixer, a kneader, and a three-roll mill.
[0120] The photocurable resin composition of the present invention is suitable for printing. If the adhesive layer is formed by applying the desired pattern on the adherend (substrate) by printing, it has the advantage of being able to omit the cutting work compared to the case where the adhesive of the desired shape is obtained by cutting the sheet-shaped adhesive just before laminating. As a result, the generation of waste can be suppressed and the environmental load can be reduced.
[0121] The lower limit of the viscosity of the photocurable resin composition of the present invention at 25°C is 0.001 Pa·s, and the upper limit is 500 Pa·s. By making the above-mentioned viscosity within this range, the photocurable resin composition of the present invention is suitable for printing. The preferred lower limit of the above-mentioned viscosity is 0.01 Pa·s, the preferred upper limit is 300 Pa·s, the more preferred lower limit is 0.1 Pa·s, and the more preferred upper limit is 100 Pa·s.
[0122] The viscosity can be measured, for example, by using VISCOMETER TV-22 (manufactured by Toki Sangyo Co., Ltd.) as an E-type viscometer and appropriately selecting a rotation speed of 1 to 100 rpm from the optimum torque number in each viscosity range using a cone plate of CP1.
[0123] For the photocurable resin composition of the present invention, the irradiation dose is set to 3000 mJ / cm 2 The photocurable resin composition was irradiated with a wavelength of 395 nm and an illumination of 500 mW / cm 2 The preferred lower limit of the gel fraction of the obtained cured product is 25% by mass, and the preferred upper limit is 60% by mass.
[0124] By setting the gel fraction of the cured product within this range, the adhesiveness and creep resistance of the obtained photocurable resin composition after curing become more excellent. The more preferred lower limit of the gel fraction of the cured product is 30% by mass, and the more preferred upper limit is 50% by mass.
[0125] In addition, the gel fraction of the above-mentioned solidified material can be measured by the following method.
[0126] That is, first, the irradiation dose was set to 3000 mJ / cm 2 The photocurable resin composition was irradiated with a wavelength of 395 nm and an illumination of 500 mW / cm 2 The solidified product was obtained by irradiating the solidified product with ultraviolet light. 0.15 g of the solidified product was weighed in a glass bottle and immersed in 30 g of tetrahydrofuran and shaken at 23°C for 24 hours. Next, the solidified product was taken out through a 200-mesh filter and heated at 110°C for 1 hour for drying. Then, the mass of the solidified product was measured and the gel fraction was calculated by the following formula.
[0127] Gel fraction (mass %) = (W2 / W1) × 100
[0128] W1: The mass of the solidified material before immersion in tetrahydrofuran at 23°C
[0129] W2: The mass of the solidified material after being immersed in tetrahydrofuran at 23°C and then taken out and dried
[0130] The photocurable resin composition of the present invention was applied on a substrate so that the irradiation dose was 3000 mJ / cm 2 The irradiation wavelength is 395nm and the illumination is 500mW / cm 2 The preferred lower limit of the glass transition temperature of the cured product is -10°C, and the preferred upper limit is 25°C. By setting the glass transition temperature of the cured product to be within this range, the adhesion of the obtained photocurable resin composition to various substrates becomes more excellent. The more preferred lower limit of the glass transition temperature of the cured product is -5°C, and the more preferred upper limit is 15°C.
[0131] In addition, the glass transition temperature of the above-mentioned cured product can be measured by the following method.
[0132] That is, first, the photocurable resin composition was applied onto a release PET film as a substrate. Then, an ultraviolet irradiation device was used to irradiate 3000 mJ / cm 2 The irradiation wavelength is 395nm and the illumination is 500mW / cm 2 The photocurable resin composition is cured by ultraviolet rays to obtain a cured product.
[0133] The obtained cured product can be measured using a dynamic viscoelasticity measuring device under the following conditions to determine the tan δ peak temperature as the glass transition temperature. As the dynamic viscoelasticity measuring device, for example, DVA-200 (manufactured by IT Instruments & Controls Co., Ltd.) can be used.
[0134] <Conditions>
[0135] Shearing
[0136] Measuring temperature: -70℃~200℃
[0137] Heating rate: 1℃ / min
[0138] Strain: 0.1%
[0139] Frequency: 1Hz
[0140] The photocurable resin composition of the present invention can be cured by irradiating ultraviolet rays to form an adhesive layer. As a method of using it, an adhesive layer can be formed on a substrate (spacer) to make an adhesive sheet that can be transferred to an adherend, or an adhesive layer can be directly formed on the adherend. In the method of directly forming an adhesive layer on an adherend, the number of laminations can be minimized, and bubbles can be prevented from entering the interface during lamination. On the other hand, in the method of forming an adhesive layer on a substrate (spacer), the adhesive layer is arranged on the adherend by transfer, so it has the advantage of less construction restrictions.
[0141] A pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer formed of a cured product of the photocurable resin composition of the present invention is also one of the present invention.
[0142] The adhesive sheet of the present invention may be an unsupported adhesive sheet without a substrate, or a supported adhesive sheet, that is, an adhesive sheet having a substrate and an adhesive layer located on at least one side of the substrate and containing a cured product of the photocurable resin composition of the present invention.
[0143] When the PSA sheet of the present invention has a substrate, it may be a single-sided PSA sheet having the PSA layer on one side of the substrate, or a double-sided PSA sheet having the PSA layers on both sides.
[0144] Examples of the substrate include sheets made of resins such as acrylic resin, olefin, polycarbonate, vinyl chloride, ABS, polyethylene terephthalate (PET), nylon, urethane, and polyimide, sheets having a mesh structure, and sheets having holes.
[0145] A method for producing a laminated body comprising the steps of printing the photocurable resin composition of the present invention and bonding an adherend using the printed photocurable resin composition is also one of the present invention.
[0146] In the method for producing the laminate of the present invention, examples of the method for printing the photocurable resin composition of the present invention include screen printing, inkjet printing, flexographic printing, gravure printing, slit coating, knife coating, spray coating, spin coating, stencil printing, dispensing, jet dispensing, reverse offset printing, etc. Among them, screen printing, inkjet printing or flexographic printing is preferred, and screen printing is more preferred.
[0147] Examples of the material of the adherend include metals such as stainless steel and aluminum, and resins.
[0148] Effects of the Invention
[0149] According to the present invention, a photocurable resin composition having excellent adhesiveness and creep resistance can be provided. In addition, according to the present invention, a pressure-sensitive adhesive sheet using the photocurable resin composition and a method for producing a laminate using the photocurable resin composition can be provided. DETAILED DESCRIPTION
[0150] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.
[0151] (Examples 1 to 13, Comparative Examples 1 to 5)
[0152] The materials were mixed according to the mixing ratios described in Tables 1 and 2 using a planetary mixer (“Awatori Rentaro” manufactured by THINKY Corporation) to obtain photocurable resin compositions of Examples and Comparative Examples.
[0153] The details of the materials described by abbreviations in the table are as follows.
[0154] (Monofunctional (meth) acrylic monomer)
[0155] ·CBA: Ethyl carbitol acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., "VISCOAT #190")
[0156] ·MEDOL-10: (2-methyl-2-ethyl-1,3-dioxolan-4-yl) methacrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd.)
[0157] ·M-140: N-acryloyloxyethyl hexahydrophthalimide (manufactured by Toagosei Co., Ltd., a nitrogen-containing ring compound)
[0158] (Multifunctional (meth)acrylic monomer)
[0159] UA-160TM: Polyether-based multifunctional urethane acrylate (manufactured by Shin-Nakamura Chemical Industry Co., Ltd.)
[0160] (Nitrogen-containing ring compounds)
[0161] ·CHMI: N-cyclohexylmaleimide (manufactured by Nippon Shokubai Co., Ltd.)
[0162] (Photopolymerization Initiator)
[0163] · Omnipol TP: polymer of ethyl (2,4,6-trimethylbenzoyl)-phenylphosphonate (manufactured by IGM Resins, polymer-type photopolymerization initiator)
[0164] · Omnipol 910: Polyethylene glycol di(β-4(4-(2-dimethylamino-2-benzyl)butyrylphenyl)piperazine)propionate (manufactured by IGM Resins, polymer-type photopolymerization initiator)
[0165] (Thermoplastic resin)
[0166] Acrylic polymer A: acrylic random copolymer (manufactured by Saiden Chemical Industry, weight average molecular weight 460,000, monomer composition (butyl acrylate and 2-ethylhexyl acrylate))
[0167] LA2330: Acrylic triblock copolymer (manufactured by Kuraray, weight average molecular weight 120,000)
[0168] Acrylic acid / styrene polymer A: styrene / butyl acrylate / styrene triblock copolymer (content of styrene-derived structures 20% by mass, weight average molecular weight 300,000, triblock ratio 90%)
[0169] Acrylic acid / styrene polymer B: styrene / butyl acrylate / styrene triblock copolymer (content of styrene-derived structures: 2.8% by mass, weight average molecular weight: 300,000, triblock ratio: 90%)
[0170] Acrylic acid / styrene polymer C: styrene / butyl acrylate / styrene triblock copolymer (content of styrene-derived structures 20% by mass, weight average molecular weight 300,000, triblock ratio 50%)
[0171] Acrylic acid / styrene polymer D: styrene / butyl acrylate / styrene triblock copolymer (content of styrene-derived structures 20% by mass, weight average molecular weight 300,000, triblock ratio 40%)
[0172] Acrylic graft polymer A: The polymer obtained in "(Synthesis of acrylic graft polymer A)" described below (weight average molecular weight 480,000), equivalent to poly(meth)acrylate
[0173] (Thickener)
[0174] ·KE-359: Rosin ester (made by Arakawa Chemical Industries, Ltd.)
[0175] ·D-6011: Rosin glycol (produced by Arakawa Chemical Industries, Ltd.)
[0176] (filler)
[0177] ·R805: Fumed silica (manufactured by NIPPON AEROSIL)
[0178] (Defoaming agent)
[0179] ·KS-66: Silicone defoamer (manufactured by Shin-Etsu Chemical Co., Ltd.)
[0180] (Synthesis of Acrylic Graft Polymer A)
[0181] A reactor equipped with a thermometer, a stirrer, and a cooling tube was prepared. After adding 73.8 parts by mass of butyl acrylate, 0.2 parts by mass of acrylic acid, 20 parts by mass of ethylene-butene macromonomer, 0.014 parts by mass of dodecyl mercaptan, and 80 parts by mass of ethyl acetate to the reactor, the reactor was heated and reflux was started. Next, 0.01 parts by mass of 1,1-bis(tert-hexylperoxy)-3,3,5-trimethylcyclohexane as a polymerization initiator was added to the reactor, and polymerization was started under reflux. Next, 0.01 parts by mass of 1,1-bis(tert-hexylperoxy)-3,3,5-trimethylcyclohexane was also added 1 hour and 2 hours after the start of polymerization, and 0.05 parts by mass of tert-hexyl peroxypivalate was added 4 hours after the start of polymerization, and the polymerization reaction was continued. Then, 8 hours after the start of polymerization, an ethyl acetate solution of acrylic graft polymer A with a solid content of 60% by mass and a weight average molecular weight of 480,000 was obtained.
[0182] The weight average molecular weight of the obtained acrylic graft polymer A is measured under the following conditions using gel permeation chromatography (manufactured by Waters, “2690 Separations Module” or the like).
[0183] <Conditions>
[0184] Solvent: Tetrahydrofuran
[0185] Sample flow rate: 1mL / min
[0186] Detector: Differential Refractometer RI
[0187] Column: GPC KF-806L (manufactured by Showa Denko K.K.)
[0188] Column temperature (measurement temperature): 40°C
[0189] Injection volume: 20 μL
[0190] (Viscosity)
[0191] 0.4 mL of each of the obtained photocurable resin compositions was collected and the viscosity was measured using VISCOMETER TV-22 (manufactured by Toki Sangyo Co., Ltd.) as an E-type viscometer with a cone and plate of CP1 at 25° C. and 10 rpm. The results are shown in Tables 1 and 2.
[0192] (Gel fraction of cured product)
[0193] Each of the obtained photocurable resin compositions was applied onto a release PET film (NIPPA, “1-E”, thickness 50 μm) using an applicator. Next, an intermittent UV LED curing device (CSS, “UV-LED PROCESSOR LSS-61”) was used to irradiate at a dose of 3000 mJ / cm 2 The irradiation wavelength is 395nm and the illumination is 500mW / cm 2 The cured product with a thickness of 50 μm was obtained by irradiating the film with ultraviolet rays. Then, the atmospheric surface was sealed with a release PET film (manufactured by NIPPA, "1-C", thickness 38 μm) to obtain a laminate.
[0194] The two release films were peeled off from the obtained laminate, and 0.15 g of the cured product of the photocurable resin composition was measured in a glass bottle, and then immersed in 30 g of tetrahydrofuran and shaken at 23° C. for 24 hours. Next, the cured product was taken out through a 200-mesh filter and heated at 110° C. for 1 hour for drying. Then, the mass of the cured product was measured, and the gel fraction was calculated by the following formula. The results are shown in Tables 1 and 2.
[0195] Gel fraction (mass %) = (W2 / W1) × 100
[0196] W1: The mass of the solidified material before immersion in tetrahydrofuran at 23°C
[0197] W2: The mass of the solidified material after being immersed in tetrahydrofuran at 23°C and then taken out and dried
[0198] (Glass transition temperature of cured product)
[0199] The two release films were peeled off from the laminate obtained by the same operation as the above "(Gel fraction of cured product)", and the cured product of the photocurable resin composition was laminated to a thickness of 1 mm, and then attached to a fixture. The dynamic viscoelasticity measurement was performed using a dynamic viscoelasticity measuring device (manufactured by IT Measurement and Control Co., Ltd., "DVA-200") under the following conditions to obtain a viscoelasticity curve. The tanδ peak temperature in the obtained viscoelasticity curve was determined as the above glass transition temperature. The results are shown in Tables 1 and 2.
[0200] <Conditions>
[0201] Shearing
[0202] Measuring temperature: -70~200℃
[0203] Heating rate: 1℃ / min
[0204] Strain: 0.1%
[0205] Frequency: 1Hz
[0206] <Evaluation>
[0207] The photocurable resin compositions obtained in the examples and comparative examples were evaluated as follows.
[0208] (180° peel adhesion)
[0209] Each of the obtained photocurable resin compositions was applied onto the inner treated surface of an adhesive polyester film (manufactured by Toyobo Co., Ltd., "Cosmoshine A4100") using an applicator. Then, without sealing the upper surface of the coating layer, an intermittent UV LED curing device (manufactured by CSS Co., Ltd., "UV-LED PROCESSOR LSS-61") was used in an atmospheric environment to irradiate 3000 mJ / cm 2 The irradiation wavelength is 395nm and the illumination is 500mW / cm 2of ultraviolet rays, thereby obtaining a cured product with a thickness of 50μm. The illuminance and cumulative light amount were measured using an ultraviolet irradiation meter UVR-T2 and a light receiving unit UD-T36T2 (manufactured by TOPCON). Next, the atmospheric surface was sealed with a release PET film (manufactured by NIPPA, "1-C", thickness 38μm), and cut in a manner to have a width of 25mm and a length of 200mm (adhered surface 25mm×125mm) to produce a laminated film. Then, the release PET film was peeled off from the laminated film, and the exposed surface was attached to the SUS substrate, and a 2kg roller was used to reciprocate once to thereby perform compression bonding to obtain a test piece. The obtained test piece was stored in an environment of 25°C for 24 hours, and a universal testing machine (manufactured by A&D, "Tensilon RTI-1310") was used to perform 180° peeling at a speed of 300mm / min, thereby measuring the 180° peeling adhesion.
[0210] (Creep resistance)
[0211] The laminate obtained by the same operation as in the above "(Gel fraction of the cured product)" was cut into 25 mm × 25 mm pieces, one release PET film (1-C) was peeled off, and the cured product was bonded to a mirror-polished SUS substrate having a width of 25 mm, a length of 100 mm, a thickness of 2 mm, and a 5 mm hole at the end of the long side. Next, the other release PET film (1-E) was peeled off, and the mirror-polished surface of the same SUS substrate was bonded to the exposed cured product surface, and then pressure-bonded at 215 N using a universal testing machine (manufactured by A&D, "Tensilon RTI-1310"), and allowed to stand at 25°C for 24 hours to obtain a test piece.
[0212] The obtained test piece was hung by hooking an S-shaped hook on one SUS substrate, and a weight of 1 kg was hung on the other SUS substrate.
[0213] This was left standing at 25° C., and the time until the weight fell was measured, and the creep resistance was evaluated according to the following criteria.
[0214] ○: Even after 48 hours, the heavy object will not fall.
[0215] △: The time until the heavy object falls is more than 24 hours and less than 48 hours
[0216] ×: The time until the heavy object falls is less than 24 hours
[0217] (Printability)
[0218] (1) Printing method
[0219] (1-1) Flexographic printing (Example 1, Comparative Example 4)
[0220] The obtained photocurable resin composition was applied to a PET film (NIPPA, “1-E”, thickness 50 μm) using a flexographic printing device (MT TECH, “Small Flexographic Printing Tester FC11”) to a thickness of 10 μm. Next, an intermittent UV LED curing device (CSS, “UV-LED PROCESSOR LSS-61”) was used to irradiate 3000 mJ / cm 2 The irradiation wavelength is 395nm and the illumination is 500mW / cm 2 The ultraviolet rays were irradiated to obtain a cured product with a thickness of 50 μm.
[0221] (1-2) Screen printing (Examples 2 to 12, Comparative Examples 1 to 3, 5)
[0222] The photocurable resin composition was applied to the inner treated surface of a PET film (NIPPA, "1-E", thickness 50 μm) using a screen printer (SERIA, "SSA-PC560E") and screen printed. The screen printing plate used was an 80-mesh printing plate that had been patterned. Next, an intermittent UV LED curing device (CSS, "UV-LED PROCESSOR LSS-61") was used to irradiate 3000 mJ / cm 2 The irradiation wavelength is 395nm and the illumination is 500mW / cm 2 The ultraviolet rays were irradiated to obtain a cured product with a thickness of 50 μm.
[0223] (1-3) Inkjet printing (Example 13)
[0224] The obtained photocurable resin composition was applied to a PET film (NIPPA, Inc., “1-E”, thickness 50 μm) using an inkjet device (Fuji Film Co., Ltd., “Materials Printer DMP-2831”) to a thickness of about 2 μm. Next, an intermittent UV LED curing device (CSS Co., Ltd., “UV-LED PROCESSOR LSS-61”) was used to irradiate 3000 mJ / cm 2 The irradiation wavelength is 395nm and the illumination is 500mW / cm 2 The ultraviolet rays are used to obtain a cured product.
[0225] (2) Evaluation of printability
[0226] Each of the obtained cured products was visually observed, and the printability was evaluated based on the following criteria.
[0227] ○: A cured product with uniform thickness and smooth surface was obtained
[0228] ×: The thickness is uneven, the surface is uneven, or there is shrinkage (Japanese: ハジキ)
[0229] [Table 1]
[0230]
[0231] [Table 2]
[0232]
[0233] Industrial Applicability
[0234] According to the present invention, a photocurable resin composition having excellent adhesiveness and creep resistance can be provided. In addition, according to the present invention, a pressure-sensitive adhesive sheet using the photocurable resin composition and a method for producing a laminate using the photocurable resin composition can be provided.
Claims
1. A photocurable resin composition, characterized in that Contains a monofunctional (meth) acrylic monomer, a multifunctional (meth) acrylic monomer, a photopolymerization initiator and a thermoplastic resin. The thermoplastic resin has a block structure or a graft structure, The photocurable resin composition has a viscosity at 25° C. of 0.001 Pa·s or more and 500 Pa·s or less.
2. The photocurable resin composition according to claim 1, wherein The thermoplastic resin includes a thermoplastic resin having a structure derived from styrene.
3. The photocurable resin composition according to claim 2, wherein The thermoplastic resin having a structure derived from styrene is a (meth)acrylic acid / styrene copolymer.
4. The photocurable resin composition according to claim 2 or 3, wherein The content ratio of the structure derived from styrene in the thermoplastic resin having a structure derived from styrene is 3% by mass or more.
5. The photocurable resin composition according to claim 1, 2 or 3, wherein The thermoplastic resin includes a triblock copolymer, and a content ratio of the triblock copolymer in the thermoplastic resin is 50% by mass or more.
6. The photocurable resin composition according to claim 1, 2 or 3, wherein The weight average molecular weight of the thermoplastic resin is 100,000 or more and 500,000 or less.
7. The photocurable resin composition according to claim 1, 2 or 3, wherein The content ratio of the thermoplastic resin in the photocurable resin composition is 1 mass % or more and 60 mass % or less.
8. The photocurable resin composition according to claim 7, wherein The content ratio of the thermoplastic resin in the photocurable resin composition is 10 mass % or more and 40 mass % or less.
9. The photocurable resin composition according to claim 1, 2 or 3, wherein The content ratio of the polyfunctional (meth)acrylic monomer in the photocurable resin composition is 0.3 mass % or more and 40 mass % or less.
10. The photocurable resin composition according to claim 1, 2 or 3, wherein The irradiation dose is 3000 mJ / cm 2 The photocurable resin composition is irradiated with a wavelength of 395 nm and an illumination of 500 mW / cm 2 The ultraviolet rays obtained by the curing process have a gel fraction of 25% by mass or more and 60% by mass or less. 11 . An adhesive sheet comprising an adhesive layer comprising a cured product of the photocurable resin composition according to claim 1 . 12 . The pressure-sensitive adhesive sheet according to claim 11 , comprising a substrate and a pressure-sensitive adhesive layer located on at least one surface of the substrate and containing a cured product of the photocurable resin composition. 13 . A method for producing a laminate, comprising: a step of printing the photocurable resin composition according to claim 1 ; and a step of attaching an adherend using the printed photocurable resin composition.
14. The method for producing a laminate according to claim 13, wherein: The photocurable resin composition is printed by screen printing, inkjet printing or flexographic printing.
Citation Information
Patent Citations
Radiation-curing adhesive composition and laminate using the same
JP2013216742A
Photocurable adhesive composition
WO2016163152A1